2021
DOI: 10.1016/j.cegh.2021.100830
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to respectful maternity care guidelines during COVID-19 pandemic and associated factors among healthcare providers working at hospitals in northwest Ethiopia: A multicenter, observational study

Abstract: Background Respectful maternity care is one of the facilitators of women's access to maternity healthcare services. However, it has been evidenced that maternal healthcare services are compromised during the pandemic of coronavirus disease 19 (COVID-19). Moreover, there was a dearth of evidence on healthcare provider's adherence to respectful maternity care guidelines through direct observation. Hence, this study intended to assess healthcare provider's adherence to respectful maternity care guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…A study conducted in northwest Ethiopia during COVID-19 found that 66% of providers did not explain procedures to birthing clients prior to performing them and 64% did not obtain consent for procedures during labor and delivery but it is unclear how these rates compare to those pre-pandemic. (14) This research offers important insights about provider adherence to respectful maternity care standards, however, there remains a notable gap in documenting client experience throughout the pandemic. Following this, the current study aimed to explore client experience of intrapartum care during the pandemic in Mozambique.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in northwest Ethiopia during COVID-19 found that 66% of providers did not explain procedures to birthing clients prior to performing them and 64% did not obtain consent for procedures during labor and delivery but it is unclear how these rates compare to those pre-pandemic. (14) This research offers important insights about provider adherence to respectful maternity care standards, however, there remains a notable gap in documenting client experience throughout the pandemic. Following this, the current study aimed to explore client experience of intrapartum care during the pandemic in Mozambique.…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 10 In recent years, numerous studies have revealed that DA is an important deterrent to service utilization. 6 , 11 18 Ethiopia’s Federal Ministry of Health has introduced the concept of RMC within the health care system to address this problem. 4…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In recent years, numerous studies have revealed that DA is an important deterrent to service utilization. 6,[11][12][13][14][15][16][17][18] Ethiopia's Federal Ministry of Health has introduced the concept of RMC within the health care system to address this problem. 4 With introduction of the RMC concept in Ethiopia, solid initiatives and efforts have been implemented to incorporate this approach into in-service training packages alongside the Basic Emergency Obstetric and Newborn Care package.…”
Section: Introductionmentioning
confidence: 99%